Obstetric violence: Comparing medical student perceptions in India and the UK. (June 2021) - Gray, Thomas; Mohan, Suruchi; Lindow, Stephen; Pandey, Uma; Farrell, Tom
Abstract: Objective(s): Obstetric Violence refers to professional deficiencies in maternity care, which can occur in both low and high resource settings. Examples include non-dignified care, lack of respect when giving care, discrimination and abandonment of care. The objective of this study was to assess knowledge and attitudes towards obstetric violence in a cohort of medical students in India and the UK. Study design: An online survey was sent to 240 UK and 280 Indian medical students. This incorporated a video showing a dramatized scenario of obstetric violence. The survey assessed participant's demographics and prior knowledge of obstetric violence. Participants scored their perceptions of eight behaviours in the video on visual analogue scales. Participants were asked to reflect on their own practice and score this. Comparisons of survey responses between UK and Indian participants were made using chi squared/Student's t -test. Results: 62 Indian medical students and 58 UK medical students completed the survey. Indian medical students were significantly more likely to be male (p < 0.001). 26 % of UK participants had previously heard the term obstetric violence, compared to 34 % of Indian participants (p = 0.15). Both were able to correctly define obstetric violence at similar rates (32 % versus 34 %). Indian medical students were significantly less critical (p < 0.001) of all eight scored behaviours in the video of obstetric violence compared to their UK counterparts. UK medical students were significantly less likely to agree that the video had changed their perception on how teams should behave and act in this context (p < 0.001). 90 % of UK participants and 38 % of Indian participants had received training in professional behaviours. 14 % of UK participants had seen examples of obstetric violence in clinical practice compared to 49 % of Indian participants. Conclusions: UK and Indian medical students were able to identify behaviours associated with obstetric violence, although the majority were previously unaware of the term. Indian medical students in this study were less critical of obstetric violence in the video, which may be because of cultural reasons, greater numbers of male students, greater exposure to obstetric violence or less training on professional behaviours. Standardised training to prevent obstetric violence should be part of undergraduate medical training internationally.